Novel object recognition of Djungarian hamsters depends on circadian time and rhythmic phenotype. (May 2015) - Müller, Lisa; Fritzsche, Peter; Weinert, Dietmar
Abstract : Circadian rhythms have been shown to influence learning and memory. In this study, cognitive functions of Djungarian hamsters revealing different circadian phenotypes were evaluated using a novel object recognition (NOR) task. Wild type (WT) animals show a clear and well-synchronized daily activity rhythm, whereas DAO hamsters are characterized by a delayed activity onset. The phenomenon is caused by a diminished ability of photic synchronization. In arrhythmic (AR) hamsters, the suprachiasmatic nuclei (SCN) do not generate a circadian signal at all. The aim of this study was to investigate consequences of these deteriorations for learning and memory processes. Hamsters were bred and kept under standardized housing conditions with food and water ad libitum and a 14 L/10 D lighting regimen. Experimental animals were assigned to different groups (WT, DAO and AR) according to their activity pattern obtained by means of infrared motion sensors. Activity onset of DAO animals was delayed by 3 ± 0.5 h. NOR tests were performed in an open arena and consisted of habituation, training (two identical objects) and test sessions (one of the two objects being replaced). The training–test interval was 60 min. Tests were performed at different Zeitgeber times (ZT 0 = light-on). Every hamster was tested at all times with an interval of one week between experiments. As activity onset of DAO animals is delaying continuously day by day, they could be tested at only three times (ZT 13, ZT 16 and ZT 19). The times animals did explore the novel and the familiar objects were recorded, and the discrimination index as a measure of cognitive performance was calculated. Behavioral analyzes revealed that, WT hamsters were able to discriminate between familiar and novel objects at ZT 13, ZT 16 and ZT 19, i.e. one hour before and during their activity period. In accordance with their delayed activity onset, DAO hamsters could discriminate between objects only at ZT 16 and ZT 19 what corresponds also to 1 h before and 2 h after their activity onset. In contrast, AR hamsters were not able to perform the NOR task at any time. The results show that the SCN modulate learning and memory in a circadian manner. Moreover, the loss of circadian rhythmicity results in cognitive impairments.